Detonation wave solutions and linear stability in a four component gas with bimolecular chemical reaction - Carvalho, Filipe (2015)
Publicado em "Mathematics of energy and climate change : International Conference and Advanced School Planet Earth". Series : CIM series in mathematical sciences, vol. 2, ISBN 978-3-319-16120-4